Evaluation of Cerebrospinal Fluid and Plasma Biomarkers for Disease Progression in Parkinson’s Disease Using a Public Dataset - Jan, Md Estiac; Datta, Oyshi; Upadhayay, Devansh; Sagar, Sajeeb Dash; Kuumar, Pushpendra; Fairoos A, Muhammed; Sharma, Himanshu (Journal of Neonatal Surgery, 2025)
Reduced levels of α-synuclein, DJ-1, and NfL in cerebrospinal fluid (CSF) and plasma, along with elevated inflammatory markers such as IL-1, IL-6, and TNF-α, have been frequently reported in Parkinson’s disease (PD). This study investigates the role of CSF and plasma biomarkers-α-synuclein, DJ-1, and Neurofilament Light Chain (NfL) using data obtained from the NeuroBioMark-PD Consortium Database, a publicly available anonymized dataset. A total of 60 participants were included: 40 PD patients and 20 healthy controls, all retained for analysis. Biomarker levels in both CSF and plasma were significantly elevated in PD patients compared to controls (p < 0.05). Strong positive correlations were observed between CSF α-synuclein and UPDRS-III motor scores (r = 0.72, p < 0.01), and between plasma DJ-1 and Hoehn and Yahr stage (r = 0.68, p < 0.01), highlighting their potential as biomarkers for disease severity and progression. These results support the clinical relevance of these biomarkers in PD diagnosis, monitoring, and potentially in guiding therapeutic strategies